2003
DOI: 10.1046/j.1365-2311.2003.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and feeding‐induced interactions between two rice planthoppers, Sogatella furcifera and Nilaparvata lugens: effects on dispersal capability and performance

Abstract: Abstract. 1. A series of laboratory experiments was conducted to explore the effects of inter-specific interactions, both direct interactive effects and those induced through previous feeding, on the dispersal capability (proportion of macropterous adults) and performance (development time and survival) of two wing-dimorphic planthoppers, the whitebacked planthopper Sogatella furcifera and the brown planthopper Nilaparvata lugens, two pests of rice throughout Asia.2. An asymmetric effect of inter-specific crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…For example, the waxy hairs of T. longula nymphs may act to exclude the nymphs of M. scutellaris from feeding areas (Figure 4). Despite this, the insects do share some of the food resource, particularly the upper portion of the petiole as a substrate to oviposit (Sosa et al 2004(Sosa et al , 2005; Remes Lenicov and Hernández 2010); consequently exploitative competition and/or plant-mediated interaction seem to be expected (Kaplan and Denno 2007), as they were recorded on the rice planthoppers N. lugens and Sogatella furcifera (Matsumura and Suzuki 2003). Finally, there is no evidence of enemy-mediated interactions because they do not share oophagous parasitoids in their native range (Triapistyn, Sosa, and Hernández 2010;Triapitsyn and Hernández 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the waxy hairs of T. longula nymphs may act to exclude the nymphs of M. scutellaris from feeding areas (Figure 4). Despite this, the insects do share some of the food resource, particularly the upper portion of the petiole as a substrate to oviposit (Sosa et al 2004(Sosa et al , 2005; Remes Lenicov and Hernández 2010); consequently exploitative competition and/or plant-mediated interaction seem to be expected (Kaplan and Denno 2007), as they were recorded on the rice planthoppers N. lugens and Sogatella furcifera (Matsumura and Suzuki 2003). Finally, there is no evidence of enemy-mediated interactions because they do not share oophagous parasitoids in their native range (Triapistyn, Sosa, and Hernández 2010;Triapitsyn and Hernández 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a growing body of literature pertaining to induced responses to insects in rice (Karban and Chen 2007), most of this research has involved piercing-sucking insect pests or indirect resistance (Xu et al 2002;Matsumura and Suzuki 2003;Zhou et al 2003;Lou et al 2005). Rice thus remains relatively under-utilized for the study of direct induced resistance to chewing insects.…”
Section: Discussionmentioning
confidence: 99%
“…What research that has been done has primarily focused on indirect induced resistance and/or induced responses to feeding by sucking insects (Bentur and Kalode 1996;Seino et al 1996;Matsumura and Suzuki 2003;Xu et al 2002Xu et al , 2003Kanno et al 2005;Lou et al 2005;Senthil-Nathan et al 2009). Recently, however, Stout et al (2009) demonstrated direct induced resistance in rice to a chewing insect, the fall armyworm (Spodoptera frugiperda J.E.…”
Section: Introductionmentioning
confidence: 99%
“…Denno et al 2001;Matsumura and Suzuki 2003;Poniatowski and Fartmann 2011c) between populations with different colonisation histories, we studied 43 populations of M. roeselii. Only populations with high abundances were chosen as these are more likely to produce macropters (Higaki and Ando 2003;Fartmann 2009, 2011b, c).…”
Section: Colonisation History and Dispersal Capabilitymentioning
confidence: 99%
“…The clear association between macroptery and dispersal in M. roeselii (Simmons and Thomas 2004;Gardiner 2009;Hochkirch and Damerau 2009) allowed us to use the proportion of long-winged individuals as a reliable index of dispersal capability (cf. Denno et al 2001;Matsumura and Suzuki 2003;Poniatowski and Fartmann 2011c). M. roeselii is an ideal model organism for studying dispersal strategies because dispersing males are easy to detect, regardless of their wing morph, due to their noisy song (Hochkirch and Damerau 2009).…”
Section: Introductionmentioning
confidence: 99%